Foreign direct investment and incentives in Israel and Egypt - Yeo, Johnny Sheok Yeow (2011)
Foreign direct investments (FDI) in Israel and Egypt have been growing with the changing political and business climate in the region. Moody's Global Rating Guide has rated Israel and Egypt as countries viable for long term investment. Israel and Egypt have many foreign investment policies and incentives to attract foreign investments. Examples of these include financial and tax incentives, such as Approved Enterprises and Free Trade Zones. High-tech industries, such as telecommunications, computer software and biotechnology industries are areas of high growth in Israel. Besides attracting foreign funds to develop these knowledge-based industries, Israel also needs investors to bring in the necessary management skills to help build its start-up companies into international enterprises.